Studies on the effect of nitrate selective resin on the water quality and growth rate of common carp (Cyprinus carpio L.) reared in recirculating system - Koltai, Tibor; Hancz, Csaba; Magyary, István; Horn, Péter (Acta Agraria Kaposváriensis, 2002)
Intensive rearing of cultured fish species in recirculating systems is growing worldwide due to the limited capacity of outdoor rearing ponds whereas the regulations of environmental protection can be secured. The accumulation of nitrate which is a metabolic product derived from ammonia is one of the most serious problems in closed rearing systems having harmful effects on the growth rate and fecundity of fish. The nitrate level can be decreased traditionally with water exchange or filtering plants. Recently the application of nitrate selective ion exchange resin is spreading as a new technique. The main aim of our experiment was to study the efficiency of this new technique on the growth rate of common carp reared in an experimental recirculating system.
Keywords: nitrate selective resin; water quality; Cyprinus carpio